Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Basnet, S; Adhikary, P; Aryal, Bijay (Journal of Chitwan Medical College, 2013)
Chronic obstructive pulmonary disease (COPD), characterized by an airway obstruction caused by emphysema, chronic bronchitis, or both, is a common and growing clinical problem that is responsible for a substantial worldwide health burden. We present a case of a 61 years old former heavy smoker with a known case of COPD having shortness of breath which gradually increased in severity and present even at rest (MRC Grade IV) and increased purulence and volume of phlegm. Digoxin, hydrocortisone, and ceftriaxone were administered to manage the exacerbation as emergency procedure along with nebulized oxygen. The patient was nebulized with the mixture of salbutamol, ipratropium, and normal saline. Later, parenteral medication was shifted to oral therapy, i.e., antibiotic (azithromycin) and corticosteroid (prednisolone). The symptoms improved with the appropriate medication. Journal of Chitwan Medical College 2013; 3(1): 67-68 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8471